Perfil imunológico, hematológico, bioquímico e sociodemográfico de gestantes, puérperas e recém-nascidos antes e durante a pandemia da covid-19 - CUNHA, Cláudia Regina Silva dos Santos (2023)
The present work delimited about the immunological, hematological, biochemical and sociodemographic profile of pregnant women, puerperal women and newborns before and during the COVID-19 pandemic. The methodology was guided by a systematic literature review and cross-sectional observational studies that resulted in the chapters presented in this thesis. With this study, it was possible to observe that the immunological interferences of COVID-19 infection in the body of the newborn are inconclusive. However, positive correlations were found between maternal COVID-19 infection and the levels of erythrocytes, hematocrit, hemoglobin, basophils, calcium and potassium of the newborn. It was possible to infer that the main interruptions of pregnancies before and during the COVID-19 pandemic occurred mainly due to cardiovascular complications evidenced by predisposing factors such as plateletosis, anemia and vascular resistance. And that prematurity is the main factor for hospitalization of neonates in intensive care units regardless of whether public or private service is provided. Thus, with this study, it is concluded that follow up studies are important for further evaluation of the repercussion of COVID-19 infection on the infant immune system, including the possibility of including evaluations of complete blood counts and biochemistry of these children at the time of collection of the foot test.